1992
DOI: 10.1034/j.1600-0501.1992.030205.x
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometric and removal torque analysis for TiO2hyphen;blasted titanium implants. An experimental study on dogs.

Abstract: The aim of the present study was to compare the anchorage of TiO2-blasted screw and cylindrical implants with conventionally used machine-produced screw and cylindrical implants inserted immediately in extraction sockets on dogs. 6 adult mongrel dogs had 3rd and 4th mandibular premolars extracted bilaterally and 24 commercial pure titanium implants were placed immediately in extraction sockets and covered with mucoperiosteum. Each dog had inserted 4 implants: 1 screw implant and 1 cylindrical implant blasted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
117
0
3

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(127 citation statements)
references
References 0 publications
7
117
0
3
Order By: Relevance
“…The in vivo tests have also confirmed that roughness promotes a better bone fixation to titanium implants [5,6]. Osteoblasts have a higher probability to adhere to a rough titanium surface while fibroblasts and epithelial cells adhere mainly to very smooth surfaces [7,8]. In the literature, it has been suggested that these findings can be explained by considering that a rough implant enhances both the stress transfer and the mechanical interlocking between bone and implant.…”
Section: Introductionmentioning
confidence: 48%
See 1 more Smart Citation
“…The in vivo tests have also confirmed that roughness promotes a better bone fixation to titanium implants [5,6]. Osteoblasts have a higher probability to adhere to a rough titanium surface while fibroblasts and epithelial cells adhere mainly to very smooth surfaces [7,8]. In the literature, it has been suggested that these findings can be explained by considering that a rough implant enhances both the stress transfer and the mechanical interlocking between bone and implant.…”
Section: Introductionmentioning
confidence: 48%
“…Of all of them, perhaps the most widely used process to increase the surface roughness of Titanium and its alloys has been the blasting process [5][6][7][8][9][10]10,11]. In the blasting process, abrasive particles (alumina, rutile, SiC, ZrO 2 , SiO 2, or hydroxyapatite) are forced against the surface by a dragging fluid (usually compressed air but it can also be wet) at a fixed pressure for a certain time.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of these surface modifications on BIC and cell attachment are still being investigated for a stronger osseointegration level between implant body and bone. Comparative studies show different BIC levels changing from 13% to 80% percent [69][70][71][72][73][74][75][76][77][78][79]. BIC values may change according to the jaw, placement of the region of the implant, healing time, implant design, and surface structure [64,69,70,[72][73][74].…”
Section: Bone-implant Interfacementioning
confidence: 99%
“…It is well known that osseointegration is the key to successful dental implantation 1) and is in part regulated by the implant surface geometry 3,11) . Many previous studies have compared the influence of the surface geometry of materials on cell behavior and the characteristics of dental implants using in vivo and/or in vitro model systems to simulate the implant surface in situ 2,4,5,13,14,16,17,19,31) .…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have compared the influence of the surface geometry of materials on cell behavior and the characteristics of dental implants using in vivo and/or in vitro model systems to simulate the implant surface in situ 2,4,5,13,14,16,17,19,31) . The characteristics of the surface geometry influence cell attachment, orientation, and subsequent tissue integration in vivo 10,11,13,14,[32][33][34][35] . Much information on the interactions between cells and materials has been gained from in vitro studies using various approaches to examine the influence of surface characteristics on cell behavior; such research helps in understanding events that occur in vivo.…”
Section: Introductionmentioning
confidence: 99%